O serviço social e o enfrentamento da Aids na Paraíba: um estudo sobre a atuação profissional do assistente social à luz das equipes multidisciplinares dos serviços de diagnóstico e atendimento a portadores de HIV/Aids do município de Campina Grande-PB - Miranda, Débora Suelle Marcelino de (2012)
The AIDS Pandemic, constitutes one of the greatest scientific, individual, and social challenges, for the recent society. Thus, in order to reduce the infection cases, the Ministry of health adopts as the main strategy, the improvement of the services that provide diagnosis and treatment for all HIV positive people in our country. Campina Grande city in Paraiba state rely on specific services to provide diagnose and treatment for infected people. From such services we highlighted the Specialized assistance Service (SAE) and the counseling and testing center (CTA).Both services rely on a multidisciplinary staff in which is included the social worker who work according to the demands of the users of such services, in addiction to being fundamental to evaluate the impacts caused by the social issues in the process of Health-Disease. Thus, alongside another graduated professionals, who comprises the multidisciplinary staffs, we decided to perform such research, in order to analyze the working of the social worker in the services that provide diagnosis and treatment for HIV positive people in Campina Grande, as well as identifying the importance of the role played by the social servicing such institutions. The present study is comprised of a fieldwork research witch has a descriptive analytic character and critical nature, as well as a quantitative and qualitative approach. The sample was composed by 11 graduated professionals who comprise the acting staffs of the SAE and CTA in Campina Grande city. According to this research, the role of the social service is not only to deal with the inner institutional conflicts but also meeting all the demands that may disturb the working of the health units. Thus, we confirm that the social service intervention in such services is basically assistance. Nevertheless, because its articulation with a generalist profession, it is often committed to the consolidation of the principles of SUS. We finally hope that the results here presented enable us to realize the importance of the working of the social worker in the services that confront the HIV virus in Campina Grande (PB).